Effect of live food and artificial diets on the larval development and rearing of sea bass (Lates calcarifer) - Syafrizal (Fakulti Sains dan Teknologi, 2011)
our major experiments namely (i) effects of delayed feeding, (ii) effects of live food and artificial plankton (AP), (iii) replacement of Artemia by microencapsulated diet (MD), and (iv) use of probiotic bacteria were conducted to evaluate the growth, survival rate (SR) and development of the digestive tract of sea bass {Lates calcarifer) larvae.Delayed feeding showed that larvae could not survive when feeding was started on the 5th and 6th day after hatching (DAH). There is no significant difference in the SR and total length (TL) when the larvae were fed on the 2nd and 3rd DAH (P>0.05). Larvae fed from the 4th DAH revealed lower SR and TL compared to larvae fed from the 2nd and 3rd DAH. Histological studies showed that the intestine and liver of sea bass larvae fed from the 4th -6th DAH were not well developed. This study indicates that initial feeding should be done at least on the 3rd DAH.